2019
DOI: 10.3390/ijms20010184
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Autophagy in Sertoli Cells Is Specifically Marked at Androgen-Dependent Stages of the Spermatogenic Cycle: Potential Mechanisms and Implications

Abstract: In a recent study, we reported that acute ethanol exposure enhanced autophagy in Sertoli cells (SCs) of adult rats. However, further research is needed to clarify the specific spermatogenic stage exhibiting the highest autophagic response, the mechanisms behind such specificity, and the related relevance to sperm. This brief report provides results indicating that stages VII–VIII (androgen-dependent or spermiation stages) of the spermatogenic cycle exhibited more marked autophagic response in acute-ethanol tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
(100 reference statements)
2
20
0
1
Order By: Relevance
“…receptor expression in testis (Horibe et al, 2017;Horibe, Eid, Ito, Otsuki, & Kondo, 2019). It has been also demonstrated that testicular proteins such as steroidogenic acute regulatory (StAR) protein (Jana, Jana, De, & Guha, 2010;Radhakrishnakartha, Appu, & Indira, 2014) and cytochrome P450 side-chain cleavage enzyme (P450scc) are lower expressed in ethanol animals (Radhakrishnakartha et al, 2014).…”
mentioning
confidence: 99%
“…receptor expression in testis (Horibe et al, 2017;Horibe, Eid, Ito, Otsuki, & Kondo, 2019). It has been also demonstrated that testicular proteins such as steroidogenic acute regulatory (StAR) protein (Jana, Jana, De, & Guha, 2010;Radhakrishnakartha, Appu, & Indira, 2014) and cytochrome P450 side-chain cleavage enzyme (P450scc) are lower expressed in ethanol animals (Radhakrishnakartha et al, 2014).…”
mentioning
confidence: 99%
“…The immunohistochemical labeling methods were performed according to the manufacturer’s recommendations and our recent studies [6,18,21,22]. Paraffin-embedded sections (4-µm thickness) underwent a deparaffinization process, antigen retrieval, blocking of endogenous peroxidase activity, and non-specific antigen binding.…”
Section: Methodsmentioning
confidence: 99%
“…Using Adobe Photoshop, the tubules were captured and saved for computer analysis using Image J (National Institutes of Health, Bethesda, MA, USA). The intensity of protein expression in SCs was quantified as recently reported [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that lipophagy is involved in the testosterone biosynthesis and likely supplies endogenous energy for the development of germ cells (Ahmed et al 2016;Gao et al 2018;Ma et al 2018;Tarique et al 2019). In addition, mitophagy may have an antiapoptotic role in the ethanol-treated rat Sertoli cells (Eid et al 2012;Horibe et al 2019), and it possibly participates in the elimination of paternal mitochondria after fertilization among different species (Sato and Sato 2011;Al Rawi et al 2012;Luo et al 2013;Politi et al 2014;Rojansky et al 2016;Song et al 2016). Herein we review relevant literature concerning the role of autophagy in the male spermatogenesis and testicular endocrinology, as well as in the existence of endocrine-disrupting chemicals.…”
Section: Introductionmentioning
confidence: 99%